2005
DOI: 10.1093/jpepsy/jsj076
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Relationships of Depressive Symptoms to Pain Intensity and Functional Disability Among Children with Disease-Related Pain

Abstract: Study findings suggest that T1-depressive symptoms play a role in the longitudinal course of pain symptoms in children with JIA but not in children with SCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 36 publications
3
54
1
1
Order By: Relevance
“…We found at the individual level, associations between depression and functional disability in children with SCD, which has been observed previously 12,13,30,31 . In this study, depression significantly accounted for variance in both parent and child functional disability assessments, as well as in psychosocial HRQOL.…”
Section: Discussionsupporting
confidence: 88%
“…We found at the individual level, associations between depression and functional disability in children with SCD, which has been observed previously 12,13,30,31 . In this study, depression significantly accounted for variance in both parent and child functional disability assessments, as well as in psychosocial HRQOL.…”
Section: Discussionsupporting
confidence: 88%
“…Other studies have shown that pain characteristics do not account for a great deal of variance in global functional disability and that other factors (eg, psychological adjustment) contribute strongly to functional outcomes. 11,16,21,28,30,32,34,38 Additionally, in our specialized clinic setting there is little variability in pain reports across individuals. Perhaps in the case of school functioning, other relevant variables, for example, psychological adjustment, academic ability, parental responses, are so numerous and important that the influence of pain severity wanes in contrast.…”
Section: Discussionmentioning
confidence: 99%
“…Depression is particularly likely to contribute to school impairment in youth with chronic pain, given its strong contribution to overall functional impairment in this population 2,11,16,28 and its known effects on school functioning in other adolescent populations. 12,18,25 An additional area for future research is to assess and understand learning abilities among adolescents with chronic pain; possibly, premorbid subtle learning differences play a role in the pain-school avoidance cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Third, explained variance rates were very small. Other factors, both child-related factors, such as depression (Hoff et al, 2006;Gauntlett-Gilbert and Eccleston, 2007) and parent-related factors, such as parental attention to their child's pain (Chambers et al, 2002) need to be taken into account. Fourth, this study was designed conceptually and specifically to focus on the effects of specific variables.…”
Section: Discussionmentioning
confidence: 99%